Igualdade de género e práticas de gestão de recursos humanos - Silva, Carla (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Assuming that there are asymmetries and imbalances between women and men in the organizations, motivated by difficulties in reconciling professional, family and personal life, which if overtaken by conciliatory human resources management practices may generate benefits for workers and companies, this work intends to present a case study to evaluate the contribution of human resources management for the promotion of gender equality, in terms of reconciling professional, family and personal life. In this manner, we aim to characterize the human resources management practices promoting gender equality in the port setor company, and to analyze the perception and the difficulties that workers have in reconciling work, family and personal life. The preparation of this case study required the use of several techniques to collect qualitative data through analysis of public documents of the company, and techniques to collect quantitative data by applying a questionnaire to the universe of company workers. With this research a series of relevant results were obtained, which can help human resources management to further contribute to the needs of reconciling professional, family and personal life, and contribute to promote benefits for the organizations in the implementation of practices enhancing gender equality.